Predictive value of soluble suppression of tumourigenicity 2 on myocardial reperfusion. Issue 8 (6th August 2020) - Bai, Shiru; Liu, Huiliang; Wu, Haibo; Wang, Xuechao; Li, Ruyi; Li, Xiangming; Li, Xinning; Zhang, Lina; Chen, Tianlei; Du, Rongpin
Abstract: Background: High baseline level of soluble suppression of tumourigenicity 2 (sST2) was an independent predictor of cardiovascular death and heart failure in ST‐segment elevation myocardial infarction (STEMI). Aims: To investigate the value of serum sST2 baseline levels in predicting myocardial reperfusion in patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods: Consecutive STEMI patients who underwent PPCI within 12 h after the onset of chest pain were enrolled, and were divided into Thrombolysis In Myocardial Infarction (TIMI) myocardial perfusion grading (TMPG) 0/1/2 group and TMPG 3 group based on post‐procedural TMPG. Baseline clinical characteristics, lesions and procedural characteristics were compared. Univariate logistic regression and multivariate linear logistic analysis were performed to identify independent predictors of impaired myocardial reperfusion (TMPG 0/1/2). Receiver‐operating characteristics curve (ROC) analysis of sST2 was performed to identify the optimum cut‐off value for predicting the myocardial reperfusion. Results: A total of 121 patients was enrolled in this study. Univariate logistic regression analysis showed that Killip II–III, high levels of sST2 and brain natriuretic peptide were risk factors of TMPG 0/1/2. Multivariable logistic regression analysis revealed that sST2 was an independent predictor of impaired myocardial reperfusion (odds ratio 12.318, 95% confidence interval 4.567–33.220, P < 0.001). ROC curve analysis showed that the area under curve of sST2 was 0.849, and the best cut‐off value was 2.003 ng/mL, with a sensitivity of 89.2% and a specificity of 67.9%. Conclusion: The elevated levels of sST2 on admission were associated with impaired myocardial reperfusion in STEMI patients undergoing PPCI.